The Intergenerational Mobility of Immigrants - Borjas, George J. (Journal of Labor Economics, 1993)
This article analyzes the intergenerational mobility of immigrants. Using the 1940-70 censuses, the study reveals an important link between the earnings of immigrants and the earnings of their American-born children. Although there is some regression toward the mean, the earnings of second-generation Americans are strongly affected by variables describing economic conditions in the source countries of their parents. Current immigration policy, therefore, not only determines how immigrants perform in the labor market but also determines tomorrow's differences in the labor market experiences of American-born ethnic groups.